Circulating Senescent T Cells Are Linked to Systemic Inflammation and Lesion Size During Human Cutaneous Leishmaniasis - Covre, Luciana P.; Martins, Régia F.; Devine, Oliver P.; Chambers, Emma S.; Vukmanovic-Stejic, Milica; Silva, Juliana A.; Dietze, Reynaldo; Rodrigues, Rodrigo R.; de Matos Guedes, Herbert L.; Falqueto, Aloísio; Akbar, Arne N.; Gomes, Daniel C. O. (Frontiers in Immunology, 2019)
Leishmania (Viannia) braziliensis induces American tegumentary leishmaniasis that ranges in severity from the milder form, cutaneous (CL) to severe disseminated cutaneous leishmaniasis. Patients with CL develop a cell-mediated Th1 immune response accompanied by production of inflammatory cytokines, which contribute to parasite control and pathogenesis of disease. Here, we describe the accumulation of at circulating T cells with multiple features of telomere dependent-senescence including elevated expression of CD57, KLRG-1 and γH2AX that have short telomeres and low hTERT expression during cutaneous L. braziliensis infection. This expanded population of T cells was found within the CD45RA+CD27- (EMRA) subset and produced high levels of inflammatory cytokines, analogous to the senescence-associated secretory profile (SASP) that has been described in senescent non-lymphoid cells. There was a significant correlation between the accumulation of these cells and the extent of systemic inflammation, suggesting that they are involved in the inflammatory response in this disease. Furthermore, these cells expressed high level of the skin homing receptor CLA and there was a highly significant correlation between the number of these cells in the circulation and the size of the Leishmania-induced lesions in the skin. Collectively our results suggest that extensive activation during the early stages of leishmaniasis drives the senescence of T cells with the propensity to home to the skin. The senescence-related inflammatory cytokine secretion by these cells may control the infection but also induce collateral damage in this tissue and can therefore also contribute to the immunopathology in the disease.